Integrationsumgebung für verteilte objektorientierte Ingenieursysteme - Hahn, Axel

Semantisches Modell zum Aufbau von Hilfsorientierungsdiensten in einem globalen Engineering Netzwerk - Sabin, Andreas

Determination of the thermal conductivity of bonded joints - Hahn, O.; Meschut, Gerson (Welding in the World)

Bonding of Aluminium Profile joints - Hahn, O.; Meschut, Gerson (Tagungsband zur Swiss Bonding ´97)

Untersuchungen zur Wärmeleitfähigkeit und zum Festigkeits- und Alterungsverhalten von Klebverbindungen mit und ohne Füllstoffzusatz im Klebstoff - Hahn, O.; Meschut, Gerson

Encoding a Triangulation as a Permutation of its Point Set - Sohler, Christian; Denny, Markus (Proceedings of the 9th Canadian Conference on Computational Geometry)

In-line monitoring of rheological parameters with an electromagnetic flowmeter - Trächtler, Ansgar; Mesch, Franz (Proc. Frontiers in Industrial Process Tomography II, Engineering Foundation)

Ein einfaches Maß für den Informationsgehalt von Meßsystemen - Beyerer, J.; Trächtler, Ansgar (tm - Technisches Messen)

Tomographische Methoden bei der induktiven Durchflußmessung zur Bestimmung von Strömungsprofilen und -parametern - Trächtler, Ansgar; Horner, Boris; Schupp, Dietrich (tm - Technisches Messen)

Extensions of electromagnetic flow measurement to flow imaging, accurate flow rate measurement and determination of rheological parameters - Trächtler, Ansgar (Proc. XIV IMEKO World Congress)

Tomographische Methoden in der Meßtechnik - Trächtler, Ansgar (Tagungsband XI. Meßtechnisches Symposium)

A fast non-linear reconstruction technique for electrical impedance tomography - Trächtler, Ansgar (Proc. Frontiers in Industrial Process Tomography II, Engineering Foundation)

Stress Tensor Tomography Using Integrated Photoelasticity - Trächtler, Ansgar; Schupp, Dietrich (Journal of SICE)

Optimal Wormhole Routing in the (n, d)-Torus - Bock, Stefan; Meyer auf der Heide, Friedhelm; Scheideler, Christian (IPPS)

Simple, Efficient Routing Schemes for All-Optical Networks - Flammini, Michele; Scheideler, Christian (SPAA)

Themenheft: Softwaretechnik

A View-Oriented Approach to System Modelling Using Graph Transformations - Engels, Gregor; Heckel, Reiko; Taentzer, Gabriele; Ehrig, Hartmut (Proceedings European Software Engineering Conference (ESEC 1997), Zürich (Switzerland))
The idea of a combined reference model- and view-based specification approach has been proposed recently in the software engineering community. In this paper we present a specification technique based on graph transformations which supports such a development approach. The use of graphs and graph transformations supports an intuitive understanding and an integration of static and dynamic aspects on a well-defined semantical base. On this background, formal notions of view and view relation are developed and the behaviour of views is described by a loose semantics. We define a construction for automatic view integration which assumes that the dependencies between different views are described by a reference model. The views and the reference model are kept consistent manually, which is the task of a model manager. All concepts and results are illustrated at the well-known example of a banking system.

Thermooptische Effekte in Nd:YAG-Slablasern - Depke, Ralph; Knoke, Stefan; Schöne, Wolfram; Tünnermann, Andreas; Welling, H. (Verhandlungen der Deutschen Physikalischen Gesellschaft)
Vorteile von Laserkristallen in Slab-Geometrie gegenüber Stäben liegen in einer Reduktion der thermisch induzierten Linsenwirkung und der spannungsinduzierten Depolarisation durch einen zick-zack-förmigen Strahlverlauf innerhalb des Kristalls. Durch die Analyse der durch die Anordnung der Pumpquellen und die Dotierungskonzentration bestimmten Temperatur- und Spannungsverteilungen mit Hilfe eines Finite-Element-Modells und die Berechnung der resultierenden optischen Eigenschaften lassen sich die genannten Zielgrößen optimieren. Die Verfahren wurden auf am Laser Zentrum Hannover e.V. entwickelte Nd:YAG-Stab- und Slablaser angewandt und ermöglichten die Entwicklung diodengepumpter Festkörperlaser-Systeme mit Ausgangsleistungen von mehr als 750W bei guter Strahlqualität. Modellerweiterungen unter Berücksichtigung der Wechselwirkung zwischen Lasermoden und aktivem Material werden diskutiert. Diese Arbeit wird gefördert durch das BMBF, FKZ: 13 N 6361

Integrating the Specification Techniques of Graph Transformation and Temporal Logic - Heckel, Reiko; Ehrig, Hartmut; Wolter, Uwe; Corradini, Andrea (Proceedings of the 22nd International Symposium on Mathematical Foundations of Computer Science (MFCS 1997), Bratislava (Slovakia))

Einfrequenzbetrieb von Nd:YAG-Stablasersystemen hoher Ausgangsleistung - Knoke, Stefan; Depke, Ralph; Schöne, Wolfram; Brozek, O.S.; Tünnermann, Andreas; Welling, H. (Verhandlungen der Deutschen Physikalischen Gesellschaft, Weinheim (Germany))

Das ECO–PV–System - Krauter, Stefan; Duwe, H. (Zwölftes Nationales Symposium für Photovoltaische Energiewandlung, Staffelstein, 26.–28. Februar 1997, Band 1, S. 297–302.)

Lernen über das World–Wide–Web am Beispiel der Sonnenenergienutzung - Krauter, Stefan (Telelearning: Aufgabe und Chance für Bildung und Gesellschaft)

Reflection-Losses at Structured PV-Modules - Kerst, U.; Krauter, Stefan; Hanitsch, Rolf (Proceedings of the 14th European Photovoltaic Solar Energy Conference, Barcelona (Spanien), 30. Juni – 4. Juli 1997, S. 232–235)

Loose Semantics and Constraints for Graph Transformation Systems - Heckel, Reiko; Ehrig, Hartmut; Wolter, Uwe; Corradini, Andrea

A 2-Categorical Presentation of Distributed Graph Transformation - Gadducci, Fabio; Heckel, Reiko (Proceedings of the Workshop on the General Theory of Graph Transformation Systems (GETGRATS 1997), Bordeaux (France))

Combining Graph Transformations with Temporal Logic - Gadducci, Fabio; Heckel, Reiko; Koch, Manuel (Proceedings of the Workshop on the General Theory of Graph Transformation Systems (GETGRATS 1997), Bordeaux (France))

An Inductive View of Graph Transformation - Gadducci, Fabio; Heckel, Reiko (Proceedings of the 12th International Workshop on Recent Trends in Algebraic Development Techniques (WADT 1997), Tarquinia (Italy))

Compositional Development and Verification of Graph Transformation Systems Based on Views and View Integration - Heckel, Reiko (Proceedings of the Workshop on the General Theory of Graph Transformation Systems (GETGRATS 1997), Bordeaux (France))

Personalwirtschaftliche Strategien im europäischen Vergleich – Eine Analyse organisations- und landesspezifischer Prädiktoren - Weber, W; Kabst, Rüdiger (Personal als Strategie)

New Developments in Labour Flexibility - Mayne, L; Valverde, M A I; Brewster, C; Kabst, Rüdiger (New Developments in Labour Flexibility, Special Issue, Employee Relations: The International Journal)

Medienentwicklung - Theoretische Modellierung und fachdidaktisch ausgerichtete Anwendung - Kremer, H.-Hugo

Guest Editors' Introduction - Engels, Gregor; Jürgen Schneider, Hans (International Journal on Software Engineering and Knowledge Engineering (IJSEKE))

A Combined Reference Model- and View-Based Approach to System Specification - Engels, Gregor; Heckel, Reiko; Taentzer, Gabriele; Ehrig, Hartmut (Int. Journal of Software and Knowledge Engeneering)
The idea of a combined reference model- and view-based specification approach has been proposed recently in the software engineering community. In this paper we present a specification technique based on graph transformations which supports such a development approach. The use of graphs and graph transformations allows to satisfy the general requirements of an intuitive understanding and the integration of static and dynamic aspects on a well-defined and sound semantical base. On this background, formal notions of view and view relation are developed and the behaviour of views is described by a loose semantics. View relations are shown to preserve the behaviour of views. Moreover, we define a construction for the automatic integration of views which assumes that the dependencies between different views are described by a reference model. The views and the reference model are kept consistent manually, which is the task of a model manager. In case of more than two views more general scenarios are developed and discussed. We are able to show that the automatic view integration is compatible with the loose semantics, i.e., the behaviour of the system model is exactly the integration of the behaviours of the views. All concepts and results are illustrated at the well-known example of a banking system.

Algebraic Approaches to Graph Transformation, Part II: Single Pushout Approach and Comparison with Double Pushout Approach - Ehrig, Hartmut; Heckel, Reiko; Korff, Martin; Löwe, Michael; Ribeiro, Leila; Wagner, Annika; Corradini, Andrea (Handbook of Graph Grammars and Computing by Graph Transformations, Volume 1: Foundations)
The algebraic approaches to graph transformation are based on the concept of gluing of graphs corresponding to pushouts in suitable categories of graphs and graph morphisms. This allows one to give not only an explicit algebraic or set theoretical description of the constructions but also to use concepts and results from category theory in order to build up a rich theory and to give elegant proofs even in complex situations. In the previous chapter we have presented an overview of the basic notions and problems common to the two algebraic approaches the double pushout DPO approach and the single pushout SPO approach and their solutions in the DPO approach. In this chapter we introduce the SPO approach to graph transformation and some of its main results. We study application conditions for graph productions and the transformation of more general structures than graphs in the SPO approach where similar generalizations have been or could be studied also in the DPO approach. Finally we present a detailed comparison of the DPO and the SPO approach especially concerning the solutions to the problems discussed for both approaches in the previous chapter.

How to represent a visual specification - Engels, Gregor; Rekers, Jan; Andries, Marc (Visual Language Theory)

Algebraic Approaches to Graph Transformation, Part I: Basic Concepts and Double Pushout Approach - Corradini, Andrea; Montanari, Ugo; Rossi, Francesca; Ehrig, Hartmut; Heckel, Reiko; Löwe, Michael (Handbook of Graph Grammars and Computing by Graph Transformation, Volume 1: Foundations)
The algebraic approaches to graph transformation are based on the concept of gluing of graphs, modelled by pushouts in suitable categories of graphs and graph morphisms. This allows one not only to give an explicit algebraic or set theoretical description of the constructions, but also to use concepts and results from category theory in order to build up a rich theory and to give elegant proofs even in complex situations. In this chapter we start with an overwiev of the basic notions common to the two algebraic approaches, the double-pushout (DPO) approach and the singlepushout (SPO) approach; next we present the classical theory and some recent development of the double-pushout approach. The next chapter is devoted instead to the single-pushout approach, and it is closed by a comparison between the two approaches.

Grundfragen der Berufsbildung - Euler, D.; Kremer, H.-Hugo; Theis, M. (Meisterprüfung - Lernen für die Praxis, Ausbilden im Handwerk)

Didaktik des Rechnungswesens - Kremer, H.-Hugo; Sloane, Peter F. E. (Erziehungswissenschaft und Beruf)

Schwingungsprüfstand zur vollautomatischen Messung von Ultraschallschwingungen in piezoelektrischen Antrieben - Goldschmidt, Stefan; Hemsel, Tobias; Krome, Jürgen; Storck, Heiner; Wallaschek, Jörg (Tagungsband zum 4. Laser Vibrometer Seminar der Polytec GmbH)

Ultrasonic motors for linear positioning tasks in automobiles - Hemsel, Tobias; Wallaschek, Jörg (Proceedings of the 30th International Symposium on Automotive Technology & Automation (ISATA))
Piezoelectric ultrasonic motors are a new kind of actuators that produce high driving-forces related to their volume. Beside rotary drives like the travelling wave motor many linear drives have been developed and are already commercially available today. These motors can provide static holding-forces and driving-forces of up to 30 N at velocities of up to 220 mm/s. These operational characteristics, which are expected to be improved continuously, make these devices attractive as direct-drives for sliding roofs or windows in automobiles. In this contribution a short outline of the present state-of-the-art of linear ultrasonic motors is given. Different operating principles are compared with respect to the potential driving-force and power. Finally the working-principle of a newly developed motor, which uses the piezoelectric d33-effect, is explained in detail. Theoretical and experimental results show that this motor is capable of achieving high driving-force and rated output-power

Piezoelectric ultrasonic linear motors - Hemsel, Tobias; Wallaschek, Jörg (EUROMECH, European Mechanics Colloquium "Synthesis of Mechatronic Sytems")

Schwingungsverhalten von verstimmten Beschaufelungen mit Reibelementen - Popp, Karl; Sextro, Walter (Forschungsvereinigung Verbrennungskraftmaschinen (FW) -lnformationstagung Turbinen)

Schwingungsverhalten von Schaufelkränzen mit Reibelementen bei Frequenzverstimmung - Sextro, Walter (VDI-Reihe)

Improved reliability of bladed disks due to friction dampers - Sextro, Walter; Popp, Karl; Wolter, Ivo (The 1997 International Gas Turbine & Aeroengine Congress & Exposition)

Flexibility in European Labour Markets? The Evidence Renewed - Brewster, C; Mayne, L; Valverde, M A I; Kabst, Rüdiger (Employee Relations)

The Flexibility Paradox - Valverde, M A I; Kabst, Rüdiger; Brewster, C; Mayne, L (Employee Relations)

Windatlas für die Kreise Holzminden, Hameln-Pyrmont und Teile der Kreise Schaumburg und Hildesheim - Bendfeld, Jörg; Gärtner, Sven Olaf; Ortjohann, Egon

Samuel Beckett's Dramatic Strategy. Audience Laughter and the Postmodernist Debate - Tönnies, Merle

Almost Invariant Sets in Chua's Circuit - Dellnitz, Michael; Junge, Oliver (International Journal of Bifurcation and Chaos)
Recently multilevel subdivision techniques have been introduced in the numerical investigation of complicated dynamical behavior. We illustrate the applicability and efficiency of these methods by a detailed numerical study of Chua's circuit. In particular we will show that there exist two regions in phase space which are almost invariant in the sense that typical trajectories stay inside each of these sets on average for quite a long time.

Exploring invariant sets and invariant measures - Dellnitz, Michael; Hohmann, Andreas; Junge, Oliver; Rumpf, Martin (Chaos: An Interdisciplinary Journal of Nonlinear Science)

A lower bound for randomized algebraic decision trees - Grigoriev, Dima; Karpinski, Marek; Meyer auf der Heide, Friedhelm; Smolensky, Roman (computational complexity)

Simulating Shared Memory in Real Time: On the Computation Power of Reconfigurable Architectures - Czumaj, Artur; Meyer auf der Heide, Friedhelm; Stemann, Volker (Information and Computation)

Optimal Tradeoffs Between Size and Slowdown for Universal Parallel Networks - Meyer auf der Heide, Friedhelm; Storch, M.; Wanka, Rolf (Theory of Computing Systems)

Dynamic data structures for realtime management of large geometric scenes - Fischer, Matthias; Meyer auf der Heide, Friedhelm; Strothmann, Willy-Bernhard (5th Annual European Symposium on Algorithms (ESA '97))
We present a data structure problem which describes the requirements of a simple variant of fully dynamic walk-through animation: We assume the scene to consist of unit size balls in R2 or higher dimensions. The scene may be arbitrarily large and has to be stored in secondary memory (discs) with relatively slow access. We allow a visitor to walk in the scene, and a modeler to update the scene by insertions and deletions of balls. We focus on the realtime requirement of animation systems: For some t (specified by the computation power of (the rendering hardware of) the graphic workstation) the data structure has to guarantee that the balls within distance t of the current visitor's position are presented to the rendering hardware, 20 times per second. Insertions and deletions should also be available to the visitor with small delay, independent of the size of the scene. We present a data structure that fulfills the above task in realtime. Its runtime is output-sensitive, i.e. linear in a quantity close to the output size of the query. We further present (preliminary) experimental results indicating that our structure is efficient in practice.

Static and dynamic data management in networks - Meyer auf der Heide, Friedhelm; Vöcking, Berthold (Euro-Par'97 Parallel Processing)

Allocating weighted jobs in parallel - Berenbrink, Petra; Meyer auf der Heide, Friedhelm; Schröder, Klaus (Proceedings of the ninth annual ACM symposium on Parallel algorithms and architectures - SPAA '97)

Communication efficient parallel searching - Bäumker, Armin; Meyer auf der Heide, Friedhelm (Solving Irregularly Structured Problems in Parallel)

An adaptive method for the approximation of the generalized cell mapping - Guder, Rabbijah; Dellnitz, Michael; Kreuzer, Edwin (Chaos, Solitons & Fractals)

Europäisches Arbeitsrecht - Konsequenzen für die betriebliche Praxis - Krimphove, Dieter (Kommunale Aufgaben und Umweltrecht)

Routing on asyncronous processor networks - Karaivazoglou, Efstratios; Meyer auf der Heide, Friedhelm (Euro-Par'97 Parallel Processing)

Exploiting locality for data management in systems of limited bandwidth - Maggs, B.M.; Meyer auf der Heide, Friedhelm; Vöcking, Berthold; Westermann, Matthias (Proceedings 38th Annual Symposium on Foundations of Computer Science)

Parallel Computing in Paderborn: The SFB 376 “Massive Parallelism — Algorithms, Design Methods, Applications” - Meyer auf der Heide, Friedhelm; Decker, Thomas (Informatik ’97 Informatik als Innovationsmotor)

Demo eines Intelligenten Diagramm Assistenten (IDIAS) - Thies, S.; Gutkauf, B.; Domik, Gitta (Proceedings 5. GI Workshop Adaptivität und Benutzermodellierung in interaktiven Softwaresystemen)

User Adaptive Presentation of Information - Gutkauf, B.; Thies, S.; Domik, Gitta (Proceedings 2nd International Symposium on Global Engineering Networking)

Glenk, Hartmut: Die eingetragene Genossenschaft, in Schriftenreihe: Praxis des Handels- und Wirtschaftsrechts Heft 7; Beck 1996 - Krimphove, Dieter (Deutsche Notar-Zeitschrift)

Rademacher, Ulf: Der Europäische Betriebsrat. Die Richtlinie 94 / 45 / EG des Rates vom 22. 4. 1994 und ihre Umsetzung in nationales Recht; Nomos: Universitätsschriften Recht 1997 - Krimphove, Dieter (Recht der Arbeit (RdA))

Eva M. K. Häußling: Soziale Grundrechte in der portugiesi-schen Verfassung von 1976; in: Beiträge zum ausländischen und vergleichenden öffentlichen Recht Bd. 10, Diss. Bonn 1996; Nomos-Verlagsgesellschaft, Baden-Baden 1997 - Krimphove, Dieter (Euro A S)

A subdivision algorithm for the computation of unstable manifolds and global attractors - Dellnitz, Michael; Hohmann, Andreas (Numerische Mathematik)

Europäisches Wirtschaftsrecht - Krimphove, Dieter; Schollmeier, Andres (Bleckmann, Europarecht)

Der Gutgläubige Erwerb von Fahrnis in den Rechtsordnungen Europas -Ein Beitrag zur Rechtsvergleichung und Europäischen Rechtsharmonisierung unter Beachtung der Grundsätze der ökonomischen Analyse des "Europäischen Sachenrechts"- - Krimphove, Dieter (Festschrift für Axel Hunscha)

A Computer Architecture to Support Qualitative Simulation in Industrial Applications - Platzner, Marco; Rinner, Bernhard; Weiss, Reinhold (e & i Elektrotechnik und Informationstechnik)

Parallel qualitative simulation - Platzner, Marco; Rinner, Bernhard; Weiss, Reinhold (Simulation Practice and Theory)

Signal Representations for Hidden Markov Model Based On-Line Handwriting Recognition - Dolfing, J.G.A.; Haeb-Umbach, Reinhold (ICASSP, Munich)
Addresses the problem of online, writer-independent, unconstrained handwriting recognition. Based on hidden Markov models (HMM), which are successfully employed in speech recognition tasks, we focus on representations which address scalability, recognition performance and compactness. 'Delayed' features are introduced which integrate more global, handwriting specific knowledge into the HMM representation. These features lead to larger error-rate reduction than 'delta' features which are known from speech recognition and even require fewer additional components. Scalability is addressed with a size-independent representation. Compactness is achieved with linear discriminant analysis. The representations are discussed and the results for a mixed-style word recognition task with vocabularies of 200 (up to 99% correct words) and 20000 words (up to 88.8% correct words) are given.

The development of a command-based speech interface for a telephone answering machine - Gamm, Stephan; Haeb-Umbach, Reinhold; Langmann, Detlev (Speech Communication)
This paper reports the design of a command-based speech interface for an answering machine or a voice mail system. Automatic speech recognition was integrated in order to facilitate the remote control and the retrieval of voice messages from any telephone in a speech-only dialogue. The design goal was that consumers would perceive the speech interface as a benefit compared with the common touch-tone interface. In this paper we will first describe the speech technology underlying the system. Then it will be shown how, based on this technology, the user interface was designed in a top-down approach. We started with the development of a concept and tested it by means of a Wizard-of-Oz simulation. After refining the concept in parallel design, it was implemented in a high-fidelity prototype. By means of qualitative user testing the design was improved in three iteration steps. The achievement of the design goal was finally verified with user tests in two countries.

Robust Speech Recognition for Wireless Networks and Mobile Telephony - Haeb-Umbach, Reinhold (Eurospeech)
The increased popularity of mobile telephony introduces both challenges and opportunitites for automatic speech recognition. ASR offers ways to simplify the use of mobile phones, notably in hands- and eyes-busy situations. However, the acoustic environment can be severely degraded and the wireless network may add additional distortions to the speech signal. This paper gives an overview of the sources of degradation and attempts to robust speech recognition for mobile communications. Emphasis is placed on approaches which are suitable for implementation in mobile terminals. Two example applications are described which illustrate the robustness issues and design considerations typical of low-cost noisy speech recognition: voice-dialling in a GSM phone and hands-free digit recognition in the car.

European Speech Databases for Telephone Applications - Hoege, H.; Tropf, H. S.; Winsky, R.; van den Heuvel, H.; Haeb-Umbach, Reinhold; Choukri, K. (ICASSP, Munich)
The SpeechDat project aims to produce speech databases for all official languages of the European Union and some major dialectal variants and minority languages resulting in 28 speech databases. They will be recorded over fixed and mobile telephone networks. This will provide a realistic basis for training and assessment of both isolated and continuous-speech utterances, employing whole-word or subword approaches, and thus can be used for developing voice driven teleservices including speaker verification. The specification of the databases has been developed jointly, and is essentially the same for each language to facilitate dissemination and use. There will be a controlled variation among the speakers concerning sex, age, dialect, environment of call, etc. The validation of all databases will be carried out centrally. The SpeechDat databases will be transferred to ELRA for distribution. The next databases to be recorded will cover East European languages.

Acoustic Front Ends for Speaker-Independent Digit Recognition in Car Environments - Langmann, Detlev; Fischer, Alexander; Wuppermann, Friedhelm; Haeb-Umbach, Reinhold; Eisele, Thomas (Eurospeech)
This paper describes speaker-independent speech recognition experiments concerning acoustic front end processing on a speech database that was recorded in 3 different cars. We investigate different feature analysis approaches (mel-filter bank, mel-cepstrum, perceptually linear predictive coding) and present results with noise compensation techniques based on spectral subtraction. Although the methods employed lead to considerable error rate reduction the error analysis shows that low signal-to-noise ratios are still a problem

Investigation of Acoustic Front Ends for Speaker-Independent Speech Recognition in the Car - Langmann, Detlev; Wuppermann, Friedhelm; Haeb-Umbach, Reinhold; Fischer, A.; Eisele, Thomas (Aachener Kolloquium on Signal Theory)

Hierarchical propagation of uncertain constraints - Hüllermeier, Eyke (in Proceedings EUFIT-97 5th European Congress on Intelligent Techniques and Soft Computing, Aachen, Germany)

Approximation of fuzzy functions - Hüllermeier, Eyke (in Proceedings 4.Internationaler Workshop Fuzzy-Neuro-Systeme. Soest Germany)

Modellierung und Simulation unsicherer dynamischer Systeme und Anwendungen in der Diagnose - Hüllermeier, Eyke (In Proceedings ASIM Fachgruppentagung Soft Computing)

A user-adaptive chart editing system based on user modeling and critiquing - Gutkauf, Bernd; Thies, Stefanie; Domik, Gitta (User Modeling)

How effective are 3D display modes? - Volbracht, Sabine; Domik, Gitta; Shahrbabaki, Khatoun; Fels, Gregor (Proceedings of the ACM SIGCHI Conference on Human factors in computing systems)

"Wir haben ein Gesetz..." rechtliche Anmerkungen zum Strafverfahren gegen Jesus - Krimphove, Dieter

A new approach to modelling and simulation of uncertain dynamical systems - Hüllermeier, Eyke (International Journal of Uncertainty, Fuzziness and Knowledge-Based Systems)

A High Resolution Investigation of the Anisotropic Electron-Positron Momentum Distribution in Diamond - Nilen, R.W.N.; Connell, S.H.; Britton, D.T.; Fischer, C.G.; Sendezera, E.J.; Schmidt, Wolf Gero; Sellschop, J.P.F.; Verwoerd, W.S. (Materials Science Forum)

KnittingFactory: An Infrastructure for Distributed Web Applications - Baratloo, A.; Karaul, M.; Karl, Holger; Kedem, Z.M. (Technical Report)

STARBIST: Scan Autocorrelated Random Pattern Generation - Tsai, Kun-Han; Hellebrand, Sybille; Rajski, Janusz; Marek-Sadowska, Malgorzata
Keywords: WORKSHOP

Synthesis of Fast On-Line Testable Controllers for Data-Dominated Applications - Hertwig, Andre; Hellebrand, Sybille; Wunderlich, Hans-Joachim
Keywords: WORKSHOP

3- and 4-critical graphs of small even order - Brinkmann, Gunnar; Steffen, Eckhard (Discrete Mathematics)

Fast Signature Segmentation on a Multi-DSP Architecture - Platzner, Marco; Peters, Liliane (Proceedings of the SPIE: Conference on Parallel and Distributed Methods for Image Processing)

Specialized Architectures for Optical Flow Computation: A Performance Comparison of ASIC, DSP, and Multi-DSP - Röwekamp, Thomas; Platzner, Marco; Peters, Liliane (Proceedings of the 8th International Conference on Signal Processing Applications & Technology (ICSPAT))

(4×2) and (2×4) reconstructions of GaAs and InP(001) surfaces - Schmidt, Wolf Gero (Applied Physics A: Materials Science & Processing)

The anisotropic electron - positron momentum distribution in diamond - Nilen, R W N; Connell, S H; Britton, D T; Fischer, C G; Sendezera, E J; Schaaff, P; Schmidt, Wolf Gero; Sellschop, J P F; Verwoerd, W S (Journal of Physics: Condensed Matter)

As on InP(110) studied within density-functional theory - Grossner, U.; Schmidt, Wolf Gero; Bechstedt, F. (Physical Review B)

Chemisorption of arsenic on InP(110) - Großner, U.; Schmidt, Wolf Gero; Bechstedt, F.; Santos, P.V.; Koopmans, B.; Esser, N. (Surface Science)

Comparison of As-rich and Sb-terminated GaAs(100)(2 × 4) reconstructions - Schmidt, Wolf Gero; Bechstedt, F. (Surface Science)

Antimony-stabilized GaAs(001)(2×4) reconstructions - Schmidt, Wolf Gero; Bechstedt, F. (Physical Review B)

Electron-positron momentum density distribution in diamond - Nilen, R.W.N.; Connell, S.H.; Schmidt, Wolf Gero; Britton, D.T.; Verwoerd, W.S.; Sellschop, J.P.F.; Shrivastava, S. (Applied Surface Science)

Investigation of low cost control schemes for a selected 3-level switched mode rectifier - Ide, P.; Froehleke, N.; Grotstollen, H. (Proceedings of Power and Energy Systems in Converging Markets)